The effect of service marketing mix towards patient satisfaction and its impact to word of mouth and revisit intention at Kania Dental Clinic through service marketing mix - Benedicta Gisela Camay Octivanny; Margaretha Pink Berlianto (Institute of Computer Science (IOCS), 2022)
Founded in 2020, Kania Dental Clinic is a private dental practice provider based in South Tangerang, Indonesia. The development of the private sector in health services in developing countries, especially big cities, is growing very rapidly. Developments and changes in health facilities make private health facilities must be able to compete with other health facilities. Therefore, private health facilities must increase their competitiveness to be able to attract patients to their health facilities and one of these competitiveness is to determine a good strategy. This study aims to determine the relationship between service marketing mix, patient satisfaction and word of mouth at the Kania dental clinic. This study used quantitative research and data collection was carried out using a questionnaire. The target population of this study was Kania dental clinic outpatients who had visited the Kania dental clinic one to two times. The number of samples was determined as many as 200 samples. The sampling technique used was purposive sampling. Partial Least Square-Structural Equation Modeling (SEM-PLS) was applied in this study. The results showed that there were 3 aspects of the service marketing mix that had a positive effect on patient satisfaction, namely, service, process and people. And patient satisfaction has a positive effect on word of mouth. This study shows how important the role of service marketing mix is ​​in increasing patient satisfaction and word of mouth. Several aspects of the service marketing mix that have a significant effect on patient satisfaction are service, process, and people. And this study also proves that there is a positive influence of patient satisfaction on word of mouth